The choice - Sparks, Nicholas (New York : Grand Central Publishing, 2007)
"Travis Parker has everything a man could want: a good job, loyal friends, even a waterfront home in small-town North Carolina. In full pursuit of the good life-- boating, swimming, and barbecues with his close buddies-- he holds the vague conviction that a serious relationship with a woman would only cramp his style. That is, until Gabby Holland moves in next door. Despite his attempts to be neighborly, the appealing redhead seems to have a grudge against him. Still, Travis can't stop trying to ingratiate himself with his new neighbor, and his persistent efforts lead them both to the doorstep of a journey that neither could have foreseen. Spanning the eventful years of young love, marriage and family, THE CHOICE ultimately confronts us with the most heartwrenching question of all: how far would you go to keep the hope of love alive?"--Back cover.
Keywords: Married people -- Fiction; Love stories